FISH CATCH COMPOSITION DURING FIVE YEARS, BY FISHERIES CO-OPERATIVE SOCIETY KUTLEHAR, FROM GOBIND SAGAR RESERVOIR (HIMACHAL PRADESH) INDIA - LAL, KRISHAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Gobind Sagar Reservoir has been created by damming River Sutlej at village Bhakra in 1963. Fisheries operations are being performed in this reservoir only by licensed fishermen. Fishermen have organized themselves in fisheries co-operative societies. Fisheries co-operative society Kutlehar is one of the fisheries co- operative societies working in its area of operations in this reservoir. After fishermen hands over their catch to their co-operative society daily, the co-operative society sells the caught fish to the concerned contractors at the rate already fixed for this purpose. State fisheries department keeps a record of sold fish in every respect. Data used in this paper was obtained from state fisheries department of Himachal Pradesh Govt. Different measures were adopted for fish conservation. Gill nets having dimensions 80 meters X 5 meters, with knot to knot mesh size more than 5 cm were used for catching the fish. No fishing was done for two months during monsoon season (close season). Current study was carried between years 2016 to 2020. In the year 2016, 22374 fish weighing 41311.3 kg was caught, by this co-operative. This catch declined to 9234 fish, weighing 17483.2 kg in year 2020. Decline in fish catch was observed during the period 2016 to 2020.